MODERN FORMS OF MARKETING COMMUNICATION IN THE 21st CENTURY (Research Bulletins of the Faculty of Economic Sciences, 2018)
This study discusses the impact of progress in the field of information and communication technologies on the marketing communication in a modern enterprise. The article was prepared on the basis of source materials: subject literature and industry reports. The paper presents the relation between the progress in the field of information and communication technologies and marketing (in particular marketing communications). Furthermore, it describes marketing communication tools related to the Internet (among other things – the use of social media) and mobile communication.
Keywords: marketing communication, mobile communication, internet marketing, social media, ICT